Optimization transdermal patch of polymer combination of chitosan and HPMC-loaded ibuprofen using factorial designs - Shaum Shiyan; Misirti Maulidia Anis Marketama; Galih Pratiwi (Universitas Ahmad Dahlan, 2021)
Ibuprofen is a non-steroidal anti-inflammatory drug that has a disadvantage in its oral use, such as gastrointestinal disorders, nausea, vomiting and gastric ulcers. Transdermal patch dosage forms are an alternative in overcoming this weakness. The transdermal patch is formulated using a special membrane that can control drug release in a matrix system. Therefore, this study optimizes chitosan and HPMC as polymers using a factorial design approach. The parameters tested included weight uniformity, patch thickness, swelling index, in vitro release rate, folding resistance, ibuprofen uniformity, surface pH, and moisture content. The interactions between the components were evaluated using Fourier transform infrared spectrophotometry-attenuated total reflectance (FTIR-ATR). The optimum concentration of chitosan was 0.5% and HPMC 6% with CV values for weight uniformity of 0.003 ± 1.202%; humidity 0.543 ± 5.595%; swelling index 4.611 ± 23,657%; thickness 0.052 ± 2.428%; surface pH 5; durability is less than 300 times and the uniformity of ibuprofen levels is 1.52 ± 2.99%. The design approach using the FFD22 obtained an effective and efficient mathematical-statistical model to determine the optimal polymer combination in the formula. As an additional instrument in design evaluation, the chemometric approach is constructive in modeling and optimization.